Mass-dependence of self-diffusion coefficients in disparate-mass binary fluid mixtures - Binas, I.; Mryglod, I. (Condensed Matter Physics, 2009)
Self-diffusion coefficients of a binary uid mixture with components differing only in their particle masses are
studied, in particular the case when mass ratio μ of light and heavy particles tends to zero. These coefficients
were calculated within the memory function formalism, using the systematic subsequence of approximations
for the relaxation times of velocity autocorrelation function. We obtained a general relation for the self-diffusion
coefficients which show polynomial dependence on the mass ratio μ. The obtained expression has a correct
Brownian limit. We developed the hierarchy of approximations for the self-diffusion coefficients that tends to
an exact result from above and below when the order of approximations increases. Дослiджуються коефiцiєнти самодифузiї бiнарних плинiв iз компонентами, що вiдрiзняються лише масами, зокрема вивчається випадок, коли спiввiдношення мас легких i важких частинок μ прямує до нуля. Цi коефiцiєнти розрахованi за допомогою формалiзму функцiй пам’ятi з використанням систематичної послiдовностi апроксимацiй для часiв релаксацiї автокореляцiйної функцiї швидкостей. Отримано загальний вираз для коефiцiєнтiв самодифузiї, що демонструють полiномiальну залежнiсть вiд спiввiдношення мас μ. Отриманий вираз має коректну броунiвську границю. Розроблено iєрархiю апроксимацiй для коефiцiєнтiв самодифузiї, що при збiльшеннi порядку апроксимацiй прямують до точного розв’язку зверху i знизу вiдповiдно.